Scarlett - Cassidy, Cathy (England Puffin, 2006)
After being expelled from yet another school in London, twelve-year-old Scarlett is sent by her exasperated mother to live with her father, stepmother, and stepsister in Ireland, where, with the help of a mysterious boy, she eventually overcomes her anger and resentment and feels part of a family again.
Keywords: Dysfunctional families -- Stepfamilies -- Ireland